Neutrophil-to-eosinophil ratio and c-reactive protein are predictors of surgery in acute diverticulitis - Marcelino, Gisela (2015)
Background: Patients with acute diverticulitis (AD) and Hinchey<III may also need surgery. Therefore, as other markers are needed to help deciding which patients should be operated on, we tried to test the value of the C-reactive protein (CRP) and of blood cell count (and their ratios). Methods: Retrospective chart review of patients admitted to our surgical department between 2009 and 2011 with the diagnosis of AD. Only cases with a computed tomography confirmation were included in the study.Results: 174 patients (147 men, 27 women, age range 24-93 years) presented with AD. 161 patients had a modified Hinchey classification <III and 17 patients were submitted to surgery (7 had Hinchey III or IV and 10 had Hinchey<III). The neutrophil-to-eosinophil ratio (NER) had the best discriminant value in deciding for a surgical procedure in the ROC (receiver operating characteristics) curve. NER discriminated non-surgical and surgical treatment with an area under the ROC curve of 0.86 (95% confidence interval (CI), 0.79-0.92). The cut-off>244.25 yielded a sensitivity of 80% (95% CI, 44-98%), a specificity of 86% (95% CI, 79-92%), a positive likelihood ratio of 5.85 (95% CI, 3.40-10.10) and a negative likelihood ratio of 0.23 (95% CI, 0.07-0.80). In fact, NER>244.25 successfully predicted 15 out of 17 cases that were operated on in our sample. Conclusions: NER is a good marker in discriminating those that should be operated on regardless of the Hinchey category. However, more studies are needed to confirm these data.